A BIBLIOMETRIC STUDY OF FINANCIAL BEHAVIOR TRENDS USING VOSVIEWER AND DATA FROM GOOGLE SCHOLAR (2014-2024) - Islami, Muslimah Nur (Jurnal Ilmiah Ekonomi Bisnis, 2024)
This research analyzes the dynamics of individual financial behavior and the factors that influence it through bibliometric methods using VOSviewer software. Bibliometrics is a mathematical method to identify academic publications related to quotations and scientific matters and intended for use in libraries. VOSviewer is used to build a network map that depicts the relationships between keywords and identifies clusters or groups of keywords that frequently appear together. This research provides insight into research trends and effective strategies for increasing financial literacy and financial inclusion. Bibliographic data was collected from academic literature related to finance during the 2014-2024 period. The results of the analysis show that financial literacy, financial behavior, and adoption of financial technology (fintech) are topics that are often discussed in the literature; financial literacy has a strong relationship with financial decision-making, leading to better saving and investment habits and reduced debt; financial behavior mostly written in the article from the US in 2015 and highest citation in 2019 from the UK. Recommendations for future research include the use of qualitative methods, longitudinal studies, and evaluation of the impact of formal and informal financial education.